PERAN KARAKTER GOTONG ROYONG DALAM MEMBANGUN INTEGRITAS SERTA RASA TANGGUNG JAWAB SISWA DI SEKOLAH DASAR - Muhammad Azhar Nawawi; Ika Yatri; Husna, Eka Septiana Nakiya; Hasanah, Hibatillah; Alvira Febriana; Marsha Atika Putri; Akmal Fadilah; Imelda Meyvita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The focus of this study is to explore how the practice of gotong royong contributes to the development of integrity and responsibility among students in schools. Gotong royong, a distinctive aspect of Indonesian culture, symbolizes collective effort. However, in contemporary times, this spirit of collective action is on the decline. Therefore, there is a pressing need for initiatives that promote collaboration to sustain its relevance. This research adopts a descriptive qualitative approach involving observations and interviews. Findings indicate that gotong royong activities, such as rotational class duties, competitions, group assignments, and Friday clean-up sessions, play a significant role in shaping students' character. These activities foster greater responsibility and honesty among students.